On-screen framing of the Amhara protests in 2016 by journalists in Ethiopia - Biset Ayalew Nigatu (Heliyon, 2023)
The main purpose of this research was to investigate the ways Amhara Television (ATV) framed the Amhara Protest and the challenges of protest framing. More specifically, the study is geared toward examining the ways the ATV journalists implemented media framing during the 2016 Amhara protest. The study was designed to a) identify the key frames utilized by ATV while covering public protests across the region, and b) spot the main internal and external obstacles to practising public protest framing in ATV. To attain these goals, a qualitative research design was employed. Media texts, individual in-depth interviews, and focus group discussions (FGD) were used to gather the data, and the data were analysed thematically. The findings indicate that ATV used the cause of the protest, the consequence of the protest, the government's response to the protest, and the solution to the protest as key frames. The station framed that a lack of good governance and development were the main factors that caused the protest, which is different from the quest of street demonstrators [6]. ATV portrayed the protest in a negative light, emphasizing the significant economic damage and human casualties it caused. Declaring a state of emergency, deep government renewal, and setting up command posts are portrayed as measures taken by the government. Furthermore, the approach to ending the public protest is portrayed as avoiding violent measures and peacefully presenting protestors' questions. To frame solutions, ATV soug ht the help of government officials, religious leaders, and Amhara region residents who support the perspective of the government and oppose the continuance of public demonstrations. Finally, Amhara's protest framing by ATV was heavily hampered by professional constraints, a lack of self-confidence, inconsistencies in institutional training, media ownership, political influence, emotional reactions from the public against ATV journalists, and a lack of collaboration from political leaders.